Dunsmuir’s Flaws Exposed: Recent Decisions on Standard of Review - Daly, Paul (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
In Dunsmuir v. New Brunswick, the Supreme Court of Canada attempted to clarify and simplify Canadian judicial review doctrine. I argue that the Court got it badly wrong, as evidenced by four of its recent decisions.The cases demonstrate that the new categorical approach is unworkable. A reviewing court cannot apply the categorical approach without reference to something like the much-maligned “pragmatic and functional” analysis factors. The categories regularly come into conflict, in that decisions could perfectly reasonably be assigned to more than one category. When conflict occurs, it must be resolved by reference to some factors external to the categorical approach.The new, single standard of reasonableness is similarly unworkable without reference to external factors. Different types of decision attract different degrees of deference, on the basis of factors that are external to the elegant elucidation of reasonableness offered in Dunsmuir. Clarification and simplicity have thus not been achieved.